Effects of Nitro-Oxidative Stress on Biomolecules: Part 2—Reactive Molecular Dynamics Simulations - Zhaonan Chai; Yawei Feng; Tong Zhao; Xiaolong Wang; Maksudbek Yusupov; Maryam Ghasemitarei; Tayebeh Ghorbi; Annemie Bogaerts; Yuantao Zhang (Biomolecules, 2025)
In this review article, statistical mechanisms of oxidative modification reactions in various organic compounds under the influence of reactive oxygen species (ROS) generated by cold atmospheric plasma (CAP) are investigated and analyzed based on reactive molecular dynamics (MD) simulations. As an efficient and hygienic advanced oxidation technology, CAP demonstrates tremendous potential in fields such as biomedicine and environmental protection. Through simulations, this paper provides a detailed analysis of the interaction mechanisms between ROS and components of biological tissues and environmental toxins. In this paper, we review the reactions involving four major ROS (OH radicals, O atoms, <semantics>O3</semantics> molecules, and <semantics>H2O2</semantics> molecules) and organic compounds, including proteins, DNA, polysaccharides, fatty acids, antibiotics, and mycotoxins. Atomic-level analysis reveals various oxidative modification reactions induced by ROS and their resulting products, including dehydrogenation reactions, bond-formation reactions, oxygen-addition reactions, and bond-cleavage reactions. Additionally, the study elucidates the role of active functional groups in various organic compounds, the presence of special elements, and the specific reactive nature of <semantics>H2O2</semantics>. Furthermore, the influence of different ROS species and concentrations on reaction types is explored, aiming to provide a solid theoretical foundation for the application of CAP technology in biomedicine and environmental remediation.